PENGARUH SISTEM PEMBELAJARAN BERBASIS PROYEK PADA KINERJA SISWA SMP - Tumba, Mey; Putra Pratama, Muh.; Ervianti; Hasni (Indonesian Journal of Educational Technology, 2024)
The problem in this study is the influence of project-based learning systems on student performance in science subjects. The purpose of this study to be achieved is to find out how much influence the application of a learning model based on student performance in VII SMP 1 Buntao'. This study aims to determine the effect of project-based learning systems on student performance and (2) examine the influence of project-based learning systems on student performance. This pseudo-experimental research uses a post-test-only control group design. The study population was grade VII students at SMP Buntao, and there were as many as 175 people, consisting of 5 classes. A sample of 2 (two) classes consisting of 35 people each was obtained by random group sampling. The independent variable is a learning system that consists of two dimensions, namely project-based learning and conventional learning, while the dependent variable is student performance. Questionnaire sheets and tests collected data. The data were analysed with inferential statistics. The research hypothesis was tested with Manova using the program SPSS 16.0 for Windows. The conclusions of the research are: (1) There is a positive influence of project-based learning systems on student performance; (2) The project-based learning system positively influences the performance of junior high school science education students.